Who am I now? Experiences of widowed baby boomers attending grief support groups. Issue 1 (2nd January 2016) - Hilliker, Laurel Elizabeth
Abstract: This qualitative study used a symbolic interactionist approach to explore experiences of widowed baby boomers in the mid-west United States, who attend/ed grief support groups. Results from 38 personal interviews revealed three themes: (a) the importance of a support group as a safe haven coupled with the value of sharing a similar loss; (b) challenges related to group support; and (c) fractured individual and social selves. The evidence supports the idea that grief groups are effective in aiding the widowed in bereavement but also highlights a need to adjust the structure of group programs (specific to spousal loss). Recommendations are given for providers to consider addressing restoration-oriented stress as the group progresses (in lieu of a sole emphasis on loss-oriented tension). The new structure has the potential to recognise a fractured self in widowhood to meet the needs of, provide hope for, and empower widowed survivors in a 21 st century landscape.